Dinamika Sosial Industri Batik di Seberang Kota jambi - Rizal, Azira Novia (Universitas Pahlawan Tuanku Tambusai, 2025)
The batik industry is a vital component of Indonesia’s cultural economy that plays an important role in the social and economic life of Indonesian Society. As both a cultural heritage and a source of livelihood, the Jambi batik industry faces modernization and market competition that drive significant socio-cultural transformation. This study analyzes shifts in work structures, family roles, and social networks within the Jambi batik industry, reflecting the evolving dynamics of the artisan community. Using qualitative methods with a descriptive-analytical approach, the research identifies a transition from a traditional kinship-based system to a more open, market-oriented structure. These changes appear in work relationships, family participation in production, and stronger networks among artisans, government institutions, and local communities. The study concludes that the sustainability of the Jambi batik industry depends on both economic adaptability and the community’s capacity to respond to social change while preserving cultural identity.